Antarctic nematodes survival in Martian and Lunar regolith simulants under terrestrial conditions - CESAR R.L. AMARAL; FÁBIO L.V. BONES; ANTONIO CARLOS DE FREITAS; RODRIGO GOLDENBERG-BARBOSA; MAITHÊ G.P. MAGALHÃES; LUCAS M. MOREIRA; DAFNE ANJOS; ANNA DONATO; ANTONIO AMORIM; PAULO E.A.S. CÂMARA (Anais da Academia Brasileira de Ciências)
Abstract The exploration of extraterrestrial environments has become a focal point of scientific inquiry, driven by advancements in technology and a growing interest in the potential for life beyond Earth. This study investigates the adaptability of Antarctic nematodes, known for thriving in extreme cold and isolation, to simulated Martian (MGS-1) and Lunar (LMS-1) soils. The experiment revealed differential responses in nematode survivability to the two simulants, with Lunar soil demonstrating better adaptability compared to Martian soil. Our study provides valuable insights into the potential survivability of Antarctic nematodes on real Martian and Lunar substrates with the use of the MGS-1 and the LMS-1 under terrestrial conditions. The observed results suggest differential survival responses to Lunar (6.92 ± 0.74) and Martian (5.58 ± 1.91) regolith simulants and highlight the complexity of factors influencing organismal survival. Considering their crucial role in soil food webs, and their relation with nutrient cycling and carbon dioxide emissions, the observed capacity of nematodes to thrive in Martian and Lunar regoliths positions them as potential candidates to sustain human habitats, helping on the development of in-situ resource utilization (ISRU) systems, and forming the basis for a biological life-support system to facilitate human survival in extraterrestrial environments.